2019
DOI: 10.1177/0954408919831123
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution to orifice design in a rotary valve controlled electro-hydraulic vibration exciter for high-frequency sinusoidal vibration waveform

Abstract: The present study is focused on a novel method for the acquisition of high-frequency sinusoidal vibration waveform with electro-hydraulic vibration exciter. A rotary valve controlled electro-hydraulic vibration exciter is proposed to make it easier to obtain high vibration frequency than the conventional servo valve controlled counterpart. Three common used offices are taken into consideration: rectangular orifice, triangular orifice, and semicircular orifice. Analytical solution to orifice design of shape and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Valve-controlled electro-hydraulic excitation system has a simple structure, high control accuracy, easy to realize automation and integration, and it is frequently used in engineering equipment and vibration research 6 . Valve-controlled electro-hydraulic excitation equipment have three basic structures 7 , which are classified as 2D-valve controlled 8 , slide-valve controlled 9 , 10 and rotary-valve controlled 11 , 12 . The 2D valve controlled electro-hydraulic excitation apparatus vibrates by controlling the flow of liquid 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Valve-controlled electro-hydraulic excitation system has a simple structure, high control accuracy, easy to realize automation and integration, and it is frequently used in engineering equipment and vibration research 6 . Valve-controlled electro-hydraulic excitation equipment have three basic structures 7 , which are classified as 2D-valve controlled 8 , slide-valve controlled 9 , 10 and rotary-valve controlled 11 , 12 . The 2D valve controlled electro-hydraulic excitation apparatus vibrates by controlling the flow of liquid 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [17] detailed modeling of 2D valve controlled electro-hydraulic vibration exciter, studied the vibration waveform and resonance characteristics through numerical analysis and experimental tests, proved the hydraulic resonance as an important factor affecting the excitation waveform distortion and summarized the influence law of coupling relationship between working frequency and resonant frequency on waveform distortion. Wang et al [18] designed high frequency rotary valve controlled electrohydraulic vibration exciter with three kinds of value spool oil port shapes such as rectangular, triangular, and semicircular, analyzed vibration amplitude characteristics of the three typical oil ports, proposed to evaluate the vibration waveform using harmonics theory, and designed valve core oil port shape. Additionally, experimental findings indicated that the vibration waveform harmonic distortion of rotary valve exciter is less than 1% compared with the sine wave.…”
Section: Introductionmentioning
confidence: 99%
“…is eliminated the disadvantage of insufficient high-pressure working conditions owing to the "Bernoulli effect." Wang et al [15][16][17] also investigated the flow torque on a rotary valve spool. ey studied the flow characteristics of a four-way rotary valve spool with different orifice shapes and proposed a corresponding optimized design scheme for flow force compensation.…”
Section: Introductionmentioning
confidence: 99%